1994
DOI: 10.1677/joe.0.1420171
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thyroid hormones on the growth of the atria and ventricles of the heart in immature rats

Abstract: The normal plasma concentrations of tri-iodothyronine (T3) and thyroxine (T4) increase approximately six- and fourfold respectively between the end of gestation and weaning in the rat. This early postnatal surge of thyroid hormones was experimentally modified to produce either a state of hypo- or hyperthyroidism. The growth and rates of protein turnover in the atria and ventricles of the heart were studied, 12 and 20 days postpartum, both as a function of age and of changing thyroid status. Neonatal hypothyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…These observations, along with other phenotypic changes such as an increased reliance on glucose for energy metabolism (6), suggest that the hypertrophied heart reverts to a more fetal-like state. Normally, maturation of the heart with respect to MHC and SERCA expression coincides with an increase in plasma levels of thyroid hormone shortly after birth (7,8).Recent studies have shown hypertrophy and heart failure to be associated with a decrease in circulating thyroid hormone or the development of sick thyroid syndrome (3,9). In addition, heart failure itself has been shown to be associated with a reduction in the actual number of thyroid hormone receptors in the cardiac myocyte (10-13), suggesting that even though the level of thyroid hormone may not change, the heart itself may be less responsive to signaling by thyroid hormone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These observations, along with other phenotypic changes such as an increased reliance on glucose for energy metabolism (6), suggest that the hypertrophied heart reverts to a more fetal-like state. Normally, maturation of the heart with respect to MHC and SERCA expression coincides with an increase in plasma levels of thyroid hormone shortly after birth (7,8).Recent studies have shown hypertrophy and heart failure to be associated with a decrease in circulating thyroid hormone or the development of sick thyroid syndrome (3,9). In addition, heart failure itself has been shown to be associated with a reduction in the actual number of thyroid hormone receptors in the cardiac myocyte (10-13), suggesting that even though the level of thyroid hormone may not change, the heart itself may be less responsive to signaling by thyroid hormone.…”
mentioning
confidence: 99%
“…These observations, along with other phenotypic changes such as an increased reliance on glucose for energy metabolism (6), suggest that the hypertrophied heart reverts to a more fetal-like state. Normally, maturation of the heart with respect to MHC and SERCA expression coincides with an increase in plasma levels of thyroid hormone shortly after birth (7,8).…”
mentioning
confidence: 99%
“…This presumably suggests a high level of tolerance in the rat, compared with other species andior a fundamental difference between the responsiveness of neonatal and adult animals. The latter seems unlikely since cardiac hypertrophy is expressed in response to hyperthyroidism, regardless of age (Feldman et al, 1986;Canavan et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent increases in these hormone levels appear to provoke different reactions within the different tissues. Tissues with very high rates of protein synthesis, e.g., the liver (Table 3) and lung (Holt et al, 19931, are relatively unresponsive to excess thyroid hormones, but those with low absolute rates of synthesis, e.g., the striated muscles, are the most responsive (Table 3; Canavan et al, 1994). The tissue specific nature of the induced changes in protein turnover do not appear to relate to the type of thyroid hormone receptors that are expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In both humans and rodents, the start of fetal thyroid activity is associated with a rise in cardiac contractility (Cluzeaut & Maurer-Schultze 1986, Mayhew et al 1997. Canavan et al (1994) showed that hypothyroidism significantly delayed this development of the heart, while hyperthyroidism led to the opposite result.…”
Section: Introductionmentioning
confidence: 99%